2019
DOI: 10.1093/brain/awz137
|View full text |Cite
|
Sign up to set email alerts
|

Increased creative thinking in narcolepsy

Abstract: Some studies suggest a link between creativity and rapid eye movement sleep. Narcolepsy is characterized by falling asleep directly into rapid eye movement sleep, states of dissociated wakefulness and rapid eye movement sleep (cataplexy, hypnagogic hallucinations, sleep paralysis, rapid eye movement sleep behaviour disorder and lucid dreaming) and a high dream recall frequency. Lucid dreaming (the awareness of dreaming while dreaming) has been correlated with creativity. Given their life-long privileged access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
5
22
0
1
Order By: Relevance
“…Particularly, higher dream recall frequency and lucid dreaming (Dodet et al, 2015;Rak et al, 2015). Recent work has also reported an association between narcolepsy and creativity (Lacaux et al, 2019). Narcolepsy is a chronic sleep disorder characterized by excessive daytime sleepiness, disrupted nocturnal sleep, REM sleep occurring at the onset of sleep, and cataplexy (sudden loss of skeletal muscle tone in response to strong emotional stimuli) (Singh et al, 2013).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…Particularly, higher dream recall frequency and lucid dreaming (Dodet et al, 2015;Rak et al, 2015). Recent work has also reported an association between narcolepsy and creativity (Lacaux et al, 2019). Narcolepsy is a chronic sleep disorder characterized by excessive daytime sleepiness, disrupted nocturnal sleep, REM sleep occurring at the onset of sleep, and cataplexy (sudden loss of skeletal muscle tone in response to strong emotional stimuli) (Singh et al, 2013).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…With its slow-waves and spindles, non-rapid eyes movement (NREM) sleep represents the key-phenomena in these mechanisms. However, rapid eyes movement (REM) sleep per se might favor spreading the activation of a memory trace within cortical regions, leading to a reorganization of associative networks, helping to form new associations and reaching new solutions [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Given the features of abnormal REM sleep manifestation in narcolepsy, with privileged access to sleep and dreaming, a recent study assessed whether lucid dreaming (the phenomenon of being aware of dreaming during the dream) could influence creative abilities. 6,7 The authors showed that narcolepsy patients have a higher creative potential compared to controls, both in terms of creative profile and of creative achievement. Moreover, narcoleptic patients showed an overall better creative performance in an objective test that evaluated creative abilities, in particular, they scored higher in an integrative task (measuring ideas' originality) and tended to achieve better scores in a divergent task (measuring the ability to produce multiple ideas) compared to controls.…”
Section: Introductionmentioning
confidence: 99%